The effect of antenatal depression and antidepressant treatment on placental tissue: a protein-validated gene expression study - Åsa Edvinsson; Charlotte Hellgren; Theodora Kunovac Kallak; Helena Åkerud; Alkistis Skalkidou; Elisabet Stener-Victorin; Romina Fornes; Olav Spigset; Susanne Lager; Jocelien Olivier; Inger Sundström-Poromaa (BMC, 2019)
Abstract Background Antenatal depression affects 10-20% of pregnant women. Around 2-4% of European pregnant women use antidepressant treatment, most commonly selective serotonin reuptake inhibitors (SSRIs). Poor pregnancy outcomes, such as preterm birth and low birth weight, have been described in women with antenatal depression and in pregnant women on SSRI treatment. However, the effects of antenatal depression and antidepressant treatment on the placenta are largely unknown. The aim of this work was to compare placental gene and protein expression in healthy women, women with untreated antenatal depression and women on antidepressant treatment during pregnancy. Methods Placental samples from 47 controls, 25 depressed and 45 SSRI-treated women were analysed by means of qPCR using custom-designed TaqMan low-density arrays (TLDAs) for 44 genes previously known to be involved in the pathophysiology of depression, and expressed in the placenta. Moreover, placental protein expression was determined by means of immunohistochemistry in 37 healthy controls, 13 women with untreated depression and 21 women on antidepressant treatment. Statistical comparisons between groups were performed by one-way ANOVA or the Kruskal-Wallis test. Results Nominally significant findings were noted for HTR1A and NPY2R, where women with untreated depression displayed higher gene expression than healthy controls (p < 0.05), whereas women on antidepressant treatment had similar expression as healthy controls. The protein expression analyses revealed higher expression of HTR1A in placentas from women on antidepressant treatment, than in placentas from healthy controls (p < 0.05). Conclusion The differentially expressed HTR1A, both at the gene and the protein level that was revealed in this study, suggests the involvement of HTR1A in the effect of antenatal depression on biological mechanisms in the placenta. More research is needed to elucidate the role of depression and antidepressant treatment on the placenta, and, further, the effect on the fetus.